Design of a rubble mound breakwater under the combined effect of wave heights and water levels, under present and future climate conditions. (July 2021) - Radfar, Soheil; Shafieefar, Mehdi; Akbari, Hassan; Galiatsatou, Panagiota A.; Mazyak, Ahmad Rezaee
Highlights: An approach using minimum separation time and the inter-event level criterion is proposed to select independent samples. Experiences of field projects were considered in choosing the appropriate marginals. A relatively wide range of copulas were examined and Roch-Alegre copula was selected among them. Joint probability analysis can well be incorporated in the design of rubble mound breakwaters and reduce construction costs. The proposed design approach can reduce the vulnerability of the structure against climate change effects in the future. Abstracts: Design of coastal structures without considering dependence of environmental variables can lead to over- or under estimation of their cross-sectional dimensions, imposing significant economic costs on marine projects. In this paper, the design of a conventional rubble mound breakwater at the Makran coasts on the southern coast of Iran has been carried out using a commonly applied, as well as a joint probability approach. The results of these two design methods have been compared. In this regard, joint probability analysis of water level and significant wave height has been performed. For this purpose, first an appropriate threshold was determined using a systematic and methodological approach, and then using the Copula functions, a joint probability distribution was fitted. In the next step, the critical point of the rubble mound breakwater design was determined, acting as the basis of further investigations. The results indicate that the volume of armor and filter layers of the breakwater are reduced by about 5% and 10%, respectively, which is very economically attractive for engineering projects. Also, suggestions were made for an appropriate selection of 1- and 50-year tidal levels for the common design method to be used in the design codes. Finally, the effects of climate change on the overtopping failure mechanism of the breakwater were discussed, indicating that a higher freeboard and a lower overtopping discharge in the new design approach can reduce vulnerability of the structure against climate change effects in the future.